Mental health interventions during ventricular assist device therapy: a scoping review. (25th April 2018) - Tigges-Limmer, Katharina; Brocks, Yvonne; Winkler, Yvonne; Stock Gissendanner, Scott; Morshuis, Michiel; Gummert, Jan F
Abstract: OBJECTIVES: Because of the high prevalence of psychological disorders among ventricular assist device patients, mental health support is consensually recommended. No study as yet has provided an overview of recommended and reported mental health interventions. This article presents the results of a scoping review on these questions. METHODS: We searched standard databases for relevant search criteria and found 4 consensus guidelines and 13 publications with original research mentioning mental health interventions for ventricular assist device patients. These publications are synthesized and augmented with practical recommendations from our reports and from a single-centre experience of others. RESULTS: Consensus guidelines recommend mental health interventions in 4 areas: screening and diagnostics, assessment, support and treatment and education. Interventions vary across treatment phases and by device therapy strategy, as do typical sources of mental distress. A flow chart of interventions over the course of treatment summarizes these findings. CONCLUSIONS: The delivery of consensually recommended mental health support for ventricular assist device patients involves the performance of multiple, complex tasks that vary across treatment phases. Mental health professionals should have specialized skills and should interact frequently with other caregivers in care teams.